Ben Lerner's 10:04 and climate change. Issue 7 (3rd July 2021) - Klaces, Caleb
ABSTRACT: This article shows how the formal tactics of Ben Lerner's hybrid novel, 10:04, respond to climate change. The article reads two related aspects of the text – its foregrounding of the medium and its use of appropriated images and poetry – in terms of their negotiation of a realist literary space which Amitav Ghosh has argued precludes engagement with extreme, unpredictable weather events. By focussing attention on aspects of a literary text typically overlooked in literary discussions of contemporary ecological issues, the article helps extend the purview of what it might mean for a novel to engage with a climate in crisis. This expanded understanding of engagement contributes both to the ongoing, collective exploration of contemporary climate change fiction and to the stock of critical tools with which to interpret it.